The Unintended Effects of the TCJA's Interest Deduction Limitation on the Supply Chain - Shevlin, Terry; Venkat, Aruhn; Yoo, Il Sun (Contemporary Accounting Research, 2026)
ABSTRACT We examine the effects of the 2017 Tax Cuts and Jobs Act's (TCJA) interest deduction limitation on suppliers. Using a difference‐in‐differences design, we find that suppliers with customers subject to the limitation (“affected suppliers”) report increased accounts receivable of between 11.2% and 14.9% relative to their pre‐TCJA average accounts receivable. Using a triple differences design, we provide more granular evidence by documenting that the limitation's effects on affected suppliers' accounts receivable are driven by suppliers with customers that report increased trade credit use (i.e., higher accounts payable). In cross‐sectional analyses, we find that the effects are stronger when suppliers are smaller, have higher peer product similarity, operate in industries with low entry barriers, or are in the early stage of their life cycle, consistent with suppliers with weaker bargaining power providing more trade credit to customers compared to other suppliers. Turning to supplier consequences of increased accounts receivable, we find that affected suppliers' days sales outstanding and operating cycles increase. Next, we use path analyses to find that affected suppliers experience lower cash flows and higher risks due to their increased accounts receivable. Overall, our study provides evidence that the interest deduction limitation yielded externalities on affected firms' supply chains.